Synthesis and characterization of K₂O-dolomite solid base catalysts for methyl ester production from palm oil - Muhammad, Yahaya (2020)
Biodiesel is one of the promising substitutes for petroleum-based diesel due to its numerous benefits. Generally, homogeneous catalysts are used in the methyl ester production, exhibiting better catalytic activity. However, this catalyst is associated with a number of shortcomings, these includes tedious in separation, generates a colossal amount of wastewater and difficult to recover. These economic and environmental drawbacks can be resolved with the help of heterogeneous catalysts, where they can be reused repeatedly without any major loss in their catalytic activity, making the process more economical and environmentally friendly. In this work, potassium oxide doped dolomite (K2O-dolomite) catalysts were prepared by impregnation method with a loading of 5, 10, 15 and 20 wt% K2O and labelled as 5 wt% K/D, 10 wt% K/D, 15 wt% K/D, and 20 wt% K/D, respectively. The catalysts were calcined in a static air at 850 °C for 3 hrs. X-ray diffraction (XRD) analysis of dolomite revealed the presence of calcium oxide (CaO) and magnesium oxide (MgO) phases with high crystallinity, in which intensity reduced after doped with varying concentrations of K2O. Scanning electron microscope (SEM) revealed that as more K2O was doped on dolomite, the particles became more agglomerated as opposed to a homogeneously small-sized particles on undoped sample that lead to severe decrease of BET surface area from 19.0 m2/g in dolomite to 1.3 m2/g in 20 wt% K/D. However, the high activity of the doped catalyst was dictated by the high amount of basic site, as evidenced in Temperature Programmed Desorption of carbon dioxide (TPD-CO2) which showed an increase in the capacity of the basic site with an increased amount of K2O as in the case of 15 wt% K/D. Thermo Gravimetry–Differential Thermal Gravimetry analysis (TG-DTG) of all the samples showed a similar onset degradation temperatures with three decomposition signals. Fourier Transmission infrared spectroscopy (FT-IR) confirmed the presence of CaO and MgO which corroborated well with XRD results. The transesterification reaction was optimized by Taguchi method involving four levels and five factors (reaction temperature, reaction time, methanol to oil molar ratio, catalyst amount and K2O loading). The results indicated that temperature is the most significant parameter influencing the methyl ester yield, followed by methanol to oil molar ratio, catalyst amount and K2O loading while reaction time was not a significant factor. The optimum conditions observed for maximum methyl ester yield of 98.7% were temperature 60 °C, methanol to oil molar ratio 12:1, catalyst amount 1 wt.%, K2O loading 15 wt.% and reaction time 1h. The 15 wt% K/D catalyst displayed the best catalytic performance due to its highest total basicity content. The physicochemical properties of the produced methyl ester were found to conform with the ASTM D6752 and EN1421 specification. The catalyst can still possess a rather high methyl ester yield after reused for 6 cycles with a negligible decrease in activity due to K+ ions leached into the product. Overall, doping of K2O in the catalyst has significantly improved the catalytic activity in the transesterification of palm oil.